The Journal “Higher Education in Russia”: 30 Years of Research and Reflection - L. S. Grebnev; N. S. Kirabaev; V. S. Sheinbaum; G. E. Zborovsky; M. A. Lukashenko (Высшее образование в России, 2022)
The round-table discussion dedicated to the 30th anniversary of the journal Vysshee obrazovanie v Rossii (Higher Education in Russia) took place on October 26, 2022 within the framework of XIII International conference of higher education (ICHE). Since its founding, the journal acts as a platform to discuss the urgent issues of higher education. In different periods, the researchers discussed competence-based approach, Bologna process, online education, quality of higher education, educational policy, educational management, assessment of learning outcomes, training of highly skilled researchers and teaching personnel, digitalization of education and many others. Today higher education in Russia is at a turning point of its history. We should impartially evaluate the path traveled, what has been achieved and what are the consequences. A look at the past became the subject of the round-table discussion.